Structure and packing of aminoxyl and piperidinyl acrylamide monomers. Issue 10 (1st October 2015) - Goswami, Shailesh K.; Hanton, Lyall R.; McAdam, C. John; Moratti, Stephen C.; Simpson, Jim
<x xml:space="preserve">Abstract</x> The closely related title compounds, 4‐acrylamido‐2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl, C12H21N2O2, (I), and N‐(2, 2, 6, 6‐tetramethylpiperidin‐4‐yl)acrylamide monohydrate, C12H22N2O·H2O, (II), are important monomers in the preparation of redox‐active polymers. They comprise an acrylamide group of the usual s‐cis configuration appended to a 2, 2, 6, 6‐tetramethyl‐substituted piperidine‐1‐oxyl radical or a piperidinyl chair, respectively. The adjacent amide and piperidinyl H atoms are approximately trans across the C—N bond. The packing in (I) is dominated by N—H...O hydrogen bonds; these are supported by C—H...O contacts to form an R21(6) ring repeat, a motif which has been observed in other acrylamide structures. In (II), hydrogen bonds are again key to the packing arrangements. In this case, the incorporated solvent water molecule acts as an acceptor through its O atom and as a donor through both H atoms, binding three adjacent piperidinylacrylamide molecules into layers. In both structures, weak C—H...O contacts involving the piperidinyl methyl H atoms and a proximal acrylamide carbonyl O atom extend the structure in the third dimension.